A la atención de don Ramón del Valle Inclán, de s. s. s. “Dorio de Gádex”. Sin acuse de recibo entre las dos ediciones príncipes de Luces de bohemia - González Martel, Juan Manuel (Revista de Filología Románica, 2006)
“Dorio de Gádex”, pseudonym of Antonio Rey Moliné, a writer born in Cádiz, was perpetuated by Ramón del Valle Inclán among the dramatis personae in Luces de Bohemia (1920-1924). This papers, through a letter mailed to Valle Inclán dated 1924, contribute to know the fundamental data of the biography of this Andalusian writer.